Enhancing Medical Student Confidence in Psychiatric History Taking and Mental State Examination Through Peer Support Worker Sessions - Sadra Ghazanfaripour; Oluwaseyi Opatola; Maddie Coode; Gayathri Burrah; Donna Arya (BJPsych Open, 2025)
Aims: Medical students often lack confidence in psychiatric history-taking and mental state examinations (MSEs) due to limited prior exposure. Informal feedback from Cambridge University students on placement at St Andrew’s Healthcare (STAH) highlighted the need for additional training in these areas.